Positive Youth Development and Internet Use in a Sample of Spanish Adolescents - Gómez-Baya, Diego; Grasmeijer, Anna Jean; López-Bermúdez, Esther; Gaspar de Matos, Margarida; Mendoza, Ramón (Frontiers in Pediatrics, 2022)
During COVID-19 pandemic, the use of internet in adolescent population has increased. A growing research interest has been developed about the consequences of internet use for adolescent development. Despite most studies have examine the impact of internet use in some indicators of psychological maladjustment, few studies have addressed the detrimental impact in the positive indicators of mental health. Positive Youth Development (PYD) represents a positive view of adolescent transition to adulthood which focuses on building the strengths that make young people more resistant to negative outcomes and more capable to choose a positive life direction. The present study aimed to analyze the relationships between different aspects of internet use on overall PYD in a sample of Spanish adolescents. To reach this aim, a sample of 1038 adolescents (50.1% boys, M age = 14.19, SD = 1.38), enrolled in 14 high schools in the city of Huelva (Spain), filled in some self-report measures of PYD and internet use and experience, such as the frequency of internet use on weekdays or weekend, the different uses of internet (i.e., social networks, playing online, reading, surfing or looking for information, playing or downloading music, and searching, selling or buying products), and the subjective experience using internet (i.e., acknowledgement of spending too much time playing or in the networks, and being in a bad mood if they do not play or use the networks). Results of a hierarchical regression analysis showed that the more hours using internet on weekdays the less PYD. Moreover, the experience of feeling bad when not using the networks and spending too much time with online playing were related with lower PYD. However, the use of internet for reading or looking for information had positive effect on PYD. These results suggest some implications for practice, as the need to promote an adaptive internet use, by providing a safe online context which encourages the acquisition of positive social values and life skills.